Macrophomina phaseolina EM SEMENTES DE FEIJOIROE SEU CONTROLE QUÃMICO - Fancelli, Maria Isabel; Kimati, H. (REVISTA DE AGRICULTURA, 2015)
Macrophomina phaseolina EM SEMENTES DE FEIJOIROE SEU CONTROLE QUÃMICO